De novo transcriptomic analysis of the venomous glands from the scorpion Heterometrus spinifer revealed unique and extremely high diversity of the venom peptides. (1st March 2018) - Deng, Yuchen; Gu, Jiawei; Yan, Zhenpeng; Wang, Mengdi; Ma, Chaoqun; Zhang, Jiafeng; Jiang, Guixian; Ge, Mengxiao; Xu, Shuogui; Xu, Zheng; Xiao, Liang
Abstract: Scorpion, as an ancient species, has been widely used on dozens of human diseases in traditional Chinese Medicine. Although the scorpion venom from the Buthidae family with the potent toxicity attracts more interests, toxins from the non-Buthidae family draw great attention as well because of its abundance and complexity even without harm to mammals. Moreover, several toxic components of scorpion venom have been identified as valuable scaffolds for the drug design and development. Using the Next Generation Sequencing (NGS) technique, here we reported the transcriptome of the venomous glands of Heterometrus spinifer, a non-Buthidae scorpion that only a few toxic and complete components have been identified known-to-date. The total mRNA extracted from the venomous glands of H. spinifer was subjected to illumina sequencing with a strategy of de novo assembly, and a total of 54 189 transcripts were unigenes from a total of 88 311 600 determined reads. We annotated 18 567 (34.26%) unigenes from NR database, 12 258 (22.62%) from SWISSPROT database, 11 161 (20.60%) from GO database, 10 159 (18.75%) from COG database and 5059 (9.34%) from KEGG database, respectively. 2843 unigenes were further selected against the toxin-related sub-database of SWISSPROT. After removing the redundancy, 13 common toxin-related subfamilies with 62 unigenes were manually confirmed, including 8 K-toxins, 1 calcin, 3 Imperatoxin I-like, 2 La1-like, 1 scorpin-like, 3 antimicrobial peptides, two types of protease inhibitors such as 8 Kunitz-type protease inhibitors and 3 Ascaris-type protease inhibitors, and 33 proteases including 16 serine proteinases, 7 phospholipases, 5 metalloproteases, 3 hyaluronidases and 2 phosphatases. Our report is the first transcriptomic analyses of venomous glands from the scorpion H. spinifer, serving as a public information platform for the development of novel bio-therapeutics. Highlights: The first transcriptomic analyses of venomous glands from the scorpion H. spinifer is reported. The sequences are annotated against different databases, offering different classifications in general. 62 new toxic or venom peptides were selected.